WHAT IS GOOD SCIENCE AND HOW FAR CAN IT GO? - Aragón-Vargas, Luis Fernando (Pensar en Movimiento: Revista de Ciencias del Ejercicio y la Salud, 2017)
I have seized this opportunity to share with our readers a topic, seldom discussed among human movement professionals, which is nevertheless fundamental for our scientific endeavors: philosophy of science. In this editorial I present a few introductory topics, namely, the nature of science, what are its limits, and if and how they should be managed. An attempt is also made to prepare a well-supported list of good scientific research practices. As a researcher who has done most of his work in health and human performance, my focus is on the natural sciences and, more specifically, on human movement science.